Synthesis and Spatial Structure of 3-Phenylacrylic Acid Octahydroquinolizin-1-Ylmethyl Ester and 2-(Octahydroquinolizin-1-Ylmethyl)Isoindole-1,3-Dione - Zh.S. Nurmaganbetov; O.A. Nurkenov; S.D. Fazylov; D.M. Turdybekov; Ye.V. Minayeva; G. Khabdolda; A.M. Ibraybekova; Zh.S. Tilla; K.M. Turdybekov (Eurasian Chemico-Technological Journal)
The reactions of lupinine alkaloid and its chlorine derivative with cinnamoyl chloride and 2-K-isoindole-1,3-dione were investigated to obtain 3-phenylacrylic acid octahydroquinolizin-1-ylmethyl ester and 2-(octahydroquinolizin-1-ylmethyl)isoindole-1,3-dione, respectively. The optimal conditions for carrying out the aforementioned reactions were determined, taking into account the nature of the solvent and medium. It was established that acylation of the molecule in a benzene medium, in the presence of trimethylamine, resulted in the formation of 3-phenylacrylic acid octahydroquinolizin-1-ylmethyl ester, with an 82% yield. It was demonstrated that the interaction of chlorolupinine with 2-K-isoindole-1,3-dione under Gabriel reaction conditions resulted in the formation of 2-(octahydroquinolizin-1-ylmethyl)isoindole-1,3-dione. The conformer with an axial orientation of the isoindole-1,3-dione substituent was observed to exhibit greater stability than the conformer with an equatorial orientation. The structure of the synthesized compounds was investigated by IR, 1H, and 13C NMR spectroscopy. The use of two-dimensional spectra in COSY (1H-1H) and HMQC (1H-13C) formats enabled the establishment of homo- and heteronuclear interactions, thereby confirming the structure of the compounds under investigation. The values of chemical shifts, multiplet and integrated intensity of 1H and 13C signals in one-dimensional NMR spectra of the novel compounds were determined. The crystal structures of 3-phenylacrylic acid octahydroquinolizin-1-ylmethyl ester and 2-(octahydroquinolizin-1-ylmethyl)isoindole-1,3-dione were elucidated through X-ray analysis.